Psychosocial functioning and anaesthetic requirements in patients undergoing coronary artery bypass grafting - Panagopoulou, Efharis; Maes, Stan (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF